Groups. (London : Waddington and Tooth Galleries, 1978)
Corot ; Gauguin ; Pissarro ; Signac ; Sisley ; Vuillard ; Hodgkin ; Hoyland ; Matta ; Motherwell ; Scott, T. ; Vaughan ; Cohen ; Le Corbusier ; etc.
Groups, Weddington and Tooth Galleries, London, 4 April to 28 April 1978
boek